Efektifitas Penggunaan Media E-Booklet terkait Stunting dalam Upaya Meningkatkan Pengetahuan dan Sikap Kader dan Ibu Balita di Wilayah Kerja Puskesmas Kampung Baru Kota Medan: Effectiveness of Using E-Booklet Media on Stunting to Improve Knowledge and Attitudes of Posyandu Cadres and Mothers of Toddlers in the Working Area of Kampung Baru Public Health Center Medan City - Rukmana, Erni; Sandy, Yatty Destani; Fransiari, Muhammad Edwin; Nurfazriah, Latifah Rahman (Amerta Nutrition, 2026)
Background: Stunting constitutes a protracted alimentary dysregulation precipitating irrevocable diminutions in corporeal architecture, cognitive faculty, and prospective productivity. Numerous stratagems subsist to forestall stunting, among which the participatory stewardship of Posyandu cadres and mothers of toddlers is particularly consequential, especially through the augmentation of epistemic comprehension and dispositional orientation via pedagogic instruments, namely E-Booklets. Objectives: This study evaluates the effectiveness of an E-Booklet in optimizing the knowledge and attitudes of cadres and mothers of toddlers within the Kampung Baru Health Center working area. Methods: A quasi-experimental investigation employing a pre-test and post-test schema was undertaken in Medan from May to July 2025. By means of purposive sampling, 60 participants (30 cadres and 30 mothers) were enlisted. Empirical datasets were elicited through standardized questionnaires. The interventional procedure comprised the circulation of an educational E-Booklet via WhatsApp, subsequently accompanied by virtual deliberative sessions spanning a biweekly interval. The compiled data were examined utilizing paired t-tests at a significance criterion of 0.05. Results: The results showed that the use of E-Booklets significantly increased the knowledge of cadres and mothers of toddlers regarding stunting, but did not significantly affect attitudes. The knowledge score also showed a prominent spike (n=30); the results rose from 83.58±9.70 to 89.91±9.77, summarizing the mean slightly at 6.33±6.97 (p-value<0.001). In mothers of toddlers (n=30), there was no such increase in the metric, which went from 74.58 to 79.41, an average rise of 4.8±7.30 (p-value=0.001). Conclusions: The utilization of E-Booklets substantially augments knowledge pertaining to stunting, yet does not exert a statistically significant influence upon the attitudes of cadres or mothers.